Analisis Strategis Manajemen Perencanaan Pembangunan Daerah: Studi Integrasi Kebijakan, Kapasitas Fiskal dan Partisipasi Publik di Kabupaten Tulang Bawang - Fahry Ganang Saputra; Erlin Kurniati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the dynamics of development management in Tulang Bawang Regency, particularly in integrating policy, fiscal capacity, and public participation during the transition to the 2025–2029 Regional Medium-Term Development Plan (RPJMD). The study employed a descriptive qualitative method using data triangulation techniques derived from regional planning documents, financial statistical reports, and sectoral program evaluation results. The findings reveal that Tulang Bawang Regency has achieved significant progress in regional transformation and succeeded in reducing stunting rates through the Bergerak Melayani Warga (BMW) program. However, these achievements have not been supported by strong fiscal independence, while public participation remains largely dominated by a technocratic approach. The study highlights the urgent need for reforms in digitalization-based regional revenue management and stronger substantive community involvement to ensure that future regional development becomes more independent, participatory, sustainable, and inclusive in accordance with local community aspirations. These reforms are expected to strengthen governance effectiveness and improve equitable development outcomes across all regional sectors.